PENILAIAN KUALITAS KINERJA KEUANGAN PERUSAHAAN PERBANKAN ANTARA SEBELUM DAN SESUDAH MERGER STUDI KASUS PADA PT. BANK MANDIRI, Tbk - Trihastuti, Adiati; Dewi, Margareta Seliana (JEA17: Jurnal Ekonomi Akuntansi, 2016)
This study aims to find differences on the Bank's financial performance before and after the merger as well as assessing how the development of the bank’s performance after the merger. This analysis uses CAMEL (Capital, Asset Quality, Management, Earnings, Liquidity) as an analytical tool as one uses by Bank Indonesia in assessing the performance of a bank. One of the restructuring is done by mergering four state banks into one bank, Bank Mandiri. By the merger, the government hoped to be able to operate efficiently as a financial intermediary in supporting the real sector activities in Indonesia. Prior to the merger, the four banks had negative capital. It is because the number of their PPAP were smaller than the standard at the amount of 50%. Because of this negative equity, the government, through Bank Indonesia initiated to recapitalize the four banks by doing the merger. It was intended to increase the bank's capital. The policy was also done due to the bad CAR ratio as the primary measurement of bank soundness as required by Bank Indonesia. Along with these efforts the ratio was increasing sharply from -219.51% in 1999 to 295.67% in the year of 2000. It showed that there was a health improvement of the banks, after the merger.Keywords: mergers, banks, CAMEL